Food insecurity and depressive symptoms among the freeliving elderly in selected villages in Petaling district, Selangor, Malaysia (not in KOHA) - Mesbah, Siti Farhana (2018)
Ageing population is growing faster than other population in both developed and developing countries due to the declining fertility rate and mortality rate. Health is a major concern among elderly. Food insecurity is associated with poor health and nutritional status. Elderly is one of the vulnerable groups to food insecurity. Food insecurity occurs whenever the availability and accessibility to acquire adequate and safe food in socially acceptable ways is limited or uncertain. Therefore, this study aimed to determine the prevalence of food insecurity and the factors associated with food insecurity among free-living elderly in selected villages in Petaling District, Selangor. Also, the association between food insecurity and depressive symptom among the elderly was determined in this study. In this cross-sectional study, 220 respondents aged 60 to 87 years from two selected subdistricts in Petaling District, Selangor were recruited. Information on the demographic and socioeconomic background, oral health status, social support status, comorbidity status, functional status, food security status, and depressive symptoms were collected through face-to-face interviews. The independent variable, oral health status was assessed by using Geriatric Oral Health Status (GOHAI). Social support status was measured by using six-item Lubben Social Network Scale (LSNS-6) and food security status was measured by six-item USDA Food Security Status (FSS). Elderly Cognitive Assessment Questionnaire (ECAQ) was used to measure the cognitive status and Instrumental Activity Daily Living (IADL) was used to assess the physical capacity among the respondents. Elderly Mobility Scale (EMS) and handgrip dynamometer were used to assess the mobility status and handgrip strength respectively. Chi-square test and binary logistic regression analysis were used to determine the association between factors and food insecurity. General linear model was used to determine the difference in depressive symptoms based on food security status after controlling for covariates. Prevalence of food insecurity among elderly in Petaling District was 19.5% in which 18.2% of elderly had low food security and 1.3% of elderly had very low food security. Marital status (χ2= 6.818, p <0 .01), education level (χ2= 6.242, p < 0.05), occupation status (χ2= 7.540, p < 0.05), house status (Fisher Exact test, p < 0.01), and monthly income (χ2= 9.940, p < 0.05) were significantly associated with food security status. Further, oral health status (χ2= 9.627, p < 0.01), cognitive status (Fishers Exact test, p < 0.05) and physical capacity (Fishers Exact test, p < 0.05) were significantly associated with food security status. Elderly with income below the Poverty Line Income (PLI) were two times more likely to become food insecure (AOR=2.355, 95% CI: 1.002, 5.533). Further, elderly with poor oral health status were almost three times more likely to become food insecure (AOR=2.927, 95% CI: 1.347, 6.359) while elderly living in a rented house ihad higher risk of becoming food insecure by sixfold (AOR=5.879, 95% CI: 1.331, 25.968). Food insecure elderly (3.63±1.76) had significantly higher depressive symptoms than food secure elderly (2.53±1.50) after controlling for covariates (F=15.084, p < 0.01). In conclusion, about 19.5% of elderly in Petaling District, Selangor were food insecure. Monthly income of below than PLI, living in a rented house and poor oral health status were the factors associated with food insecurity. Food insecurity was associated with depressive symptoms after controlling for social support score and mobility score. As suggestion, nutrition assistance programme was proposed to reduce the prevalence of food insecurity among the respondents. Further, oral health checkup was suggested to be part of the medical checkup. Besides that, family members were advised to stay around and provide support to the respondents in order to reduce the economic hardships as well as improve mental health.